A scientific validation of In vitro anti-inflammatory activity of Punica granatum L. by human red blood cell membrane stabilization - Kota, Karunakar; Sharma, Sandhya; Tahashildar, Jameela (International Journal of Research in Medical Sciences, 2018)
Background: In recent years there has been growing interest in therapeutic use of natural products, especially those derived from plants. P. granatum is very common dietary ingredient in many parts of India and has remarkable biological and medicinal properties. Methods: In the present study, the methanolic extract of fruit peels of Punica granatum Linn. (MEPG) were investigated for anti-inflammatory activity by simple, reliable, less toxic and less time consuming HRBC membrane stabilization method. The presentation of hypo tonicity induced HRBC membrane lysis was taken a measure of anti-inflammatory activity. Their activities were compared with standard drug diclofenac. Results: The results of the study demonstrated that P. granatum contains active constituents, which possess anti-inflammatory activity which is probably related to the inhibition of prostaglandin synthesis. Conclusions: It is concluded that methanolic extract of P. granatum fruit peel possesses significant anti-inflammatory activity and this is a possible rationale for its folkloric use as an anti-inflammatory agent.